How scientists explain disease - Thagard, Paul (Book collections on Project MUSE., 1999)
How do scientists develop new explanations of disease? How do those explanations become accepted as true? And how does medical diagnosis change when physicians are confronted with new scientific evidence? These are some of the questions that Paul Thagard pursues in this book that develops a new, integrative approach to the study of science. How Scientists Explain Disease challenges both traditional philosophy of science, which has viewed science as largely a matter of logic, and contemporary science studies that view science as largely a matter of power. Drawing on theories of distributed computing and artificial intelligence, Paul Thagard develops new models that make sense of scientific change as a complex system of cognitive, social, and physical interactions.